2022
DOI: 10.25259/sni_1134_2021
|View full text |Cite
|
Sign up to set email alerts
|

Blast-related traumatic brain injury: Report of a severe case and review of the literature

Abstract: Background: Traumatic brain injury (TBI) is a well-known brain dysfunction commonly encountered in activities such as military combat or collision sports. The etiopathology can vary depending on the context and bomb explosions are becoming increasingly common in war zones, urban terrorist attacks, and civilian criminal feuds. Blast-related TBI may cause the full severity range of neurotrauma, from a mild concussion to severe, penetrating injury. Recent classifications of the pathophysiological mechanisms comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(50 reference statements)
0
3
0
Order By: Relevance
“… 83–87 Fatal injuries represent animal mortality. 85 , 88–90 For the BINT, blood–brain barrier (BBB) permeability and oxidative stress have been the most common pathological features. The degree of BBB permeability and oxidative stress depends on the intensity of the blast; these increase with an increase in the BOP.…”
Section: Pathology Of Blast-induced Neurotrauma Using Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“… 83–87 Fatal injuries represent animal mortality. 85 , 88–90 For the BINT, blood–brain barrier (BBB) permeability and oxidative stress have been the most common pathological features. The degree of BBB permeability and oxidative stress depends on the intensity of the blast; these increase with an increase in the BOP.…”
Section: Pathology Of Blast-induced Neurotrauma Using Animal Modelsmentioning
confidence: 99%
“…Cerebral edema, intracranial hemorrhage, delayed vasospasm, perivascular damage, skull fracture, tissue damage, and intracranial hypertension have been observed in severely injured patients. 88 , 123 , 169–171 In recent years, cases of mild BINT have increased. 172–175 These studies have reported headaches, sleep disorder, poor motor skills, cognitive dysfunction, depression, and anxiety.…”
Section: Clinical and Neuroimaging Investigations In Humansmentioning
confidence: 99%
“…bTBI has a variety of injury mechanisms, resulting in its more complex clinical manifestations than general TBI [3]. Although there are many studies on various injury mechanism and treatment, no breakthrough has been made [4,5].…”
Section: Introductionmentioning
confidence: 99%